საიმპერატორო კულტის გამოვლინება და მასთან დაკავშირებული წინასწარმეტყველებები ბიზანტიაში (VIII-XIII სს) - ელიზბარაშვილი, ელისო (ლოგოსი, 2020)
The cult of the emperor in Byzantium is known to originate from ancient Rome and presents a Christianized version of it. Researchers point out that the idea and manifestations of the emperor's cult had an important role to play in shaping the iconoclasm in Byzantium. It has been repeatedly mentioned about the tight connection between Byzantine Christianity and Byzantine Imperial ceremonies, the main source of which is Constantine Porphyrogenitus’ “De Ceremoniis”. The cult of the emperor includes rituals and symbols that demonstrate that the emperor is not an ordinary human being. One of the manifestations of the Imperial cult is the prophecies associated with future emperors, and whether their rule will succeed or not. In this regard stories by Byzantine historiographers of the 8th-13th centuries are discussed in the article. There are basically two types of narratives about the emperor's prophecies: prophetic miracles – visions, dreams, events (divine intervention) – and direct prophecies of oracles and astrologers. It is not uncommon for different rulers of the empire to have similar, or even identical, legends, which would have increased the degree of persuasiveness of these narratives in the eyes of the reader of these texts, since stereotypical and repetitive character was considered as a guarantee of credibility. The prophecies tell us that becoming an emperor, whether it be a porphyrogenetic prince or a mere soldier at the head of an empire, is driven by divine will. This emphasizes the uniqueness of the future emperor, ensuring his cult.